An analysis of differential item functioning by gender in the Learning Disability Screening Questionnaire (LDSQ). (April 2015) - Murray, Aja Louise; Booth, Tom; McKenzie, Karen
Highlights: Assessing differential item functioning (DIF) is important for test fairness. DIF by gender was assessed in 6 items of the LDSQ. No DIF was found in these items. Abstract: The Learning Disability Screening Questionnaire (LDSQ;McKenzie & Paxton, 2006 ) was developed as a brief screen for intellectual disability. Although several previous studies have evaluated the LDSQ with respect to its utility as a clinical and research tool, no studies have considered the fairness of the test across males and females. In the current study we, therefore, used a multi-group item response theory approach to assess differential item functioning across gender in a sample of 211 males and 132 females assessed in clinical and forensic settings. Although the test did not show evidence of differential item functioning by gender, it was necessary to exclude one item due to estimation problems and to combine two very highly related items (concerning reading and writing ability) into a single literacy item Thus, in addition to being generally supportive of the utility of the LDSQ, our results also highlight possible areas of weakness in the tool and suggest possible amendments that could be made to test content to improve the test in future revisions.